The Role of State Administrative Law in Preventing Criminal Acts of Corruption By State Officials - Maria Yeti Andrias (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Corruption in Indonesia is a serious problem, considered an extraordinary crime because of its widespread impact, detrimental to state finances, and damaging the nation's morals and integrity. This research aims to evaluate the role of state administrative law in preventing criminal acts of corruption by state officials, identify factors that influence its effectiveness, and formulate strategies for eradicating corruption from the perspective of state administrative law. The research method used is normative juridical analysis with statutory, conceptual and comparative approaches. Research findings confirm that state administrative law plays a crucial role in preventing corruption through the formulation of clear regulations, effective supervision, and implementation of administrative sanctions. However, its effectiveness is often hampered by weak law enforcement, lack of transparency, and political interference. Factors such as accountability, transparency and bureaucratic integrity have a significant influence on the success of administrative law in fighting corruption. The recommended strategy for eradicating corruption includes strengthening supervisory institutions, increasing the level of openness, community participation, and using information technology to increase efficiency and transparency in government administration.